Analysis Of Building Reinforcement Method For Hasan Ali Yücel Elementary School In Kırıkkale - Shujairi, Mays Raheem Hendı; Çağlar, Hakan (Kirsehir Ahi Evran University, 2023)
In this study, the building reinforcement provided for Hasan Ali Yücel Elementary School located at Kırıkkale province has been analyzed. The aim is to examine the current status of the school and the work carried out, and to minimize the impact on the architecture of the building and the users. As a result of the study, it has been seen that cast-in-place curtain wall application has been selected for the reinforcement of the school. The building has 4 cast-in-place curtain wall applications, 2 30x200 and 2 30x400 cm. The application has been repeated on all floors in the same number and in the same place. Furthermore, wet floors and corridors, floor coverings, ceiling and wall paints have been renewed.
Keywords: Güçlendirme; betonarme yapılar; eğitim yapıları; hasar ve onarım; Kırıkkale; Engineering; Mühendislik; Reinforcement; reinforced concrete structures; education buildings; damage and repair